2014
DOI: 10.1111/jpc.12625
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 outbreak in Northern Sydney, 2013: Case series and initial response

Abstract: EV71 is in Australia and all clinicians seeing children in primary, secondary and tertiary care centres need to be aware of the disease, the subtle nature of initial symptoms and the potentially devastating consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…The clinical manifestations of EV71 infection were consistent with results from previous studies and showed that the majority of cases occurred in children less than 5 years of age, as has been observed in other countries [ 30 , 31 ]. Thus, infection with EV71 may become serious public health concern, particularly for children.…”
Section: Discussionsupporting
confidence: 90%
“…The clinical manifestations of EV71 infection were consistent with results from previous studies and showed that the majority of cases occurred in children less than 5 years of age, as has been observed in other countries [ 30 , 31 ]. Thus, infection with EV71 may become serious public health concern, particularly for children.…”
Section: Discussionsupporting
confidence: 90%
“…In this outbreak, there were nearly 120 severe cases reported, with EV-A71 being the predominant genotype (Fig. 1) [41, 42]. Pronounced clinical symptoms of suspected EV-A71 infection during this outbreak involved myoclonic jerks among patients with severe infection [41].…”
Section: Ev-a71 Circulation In the Asia-pacific Countriesmentioning
confidence: 99%
“…Thus, fever and infectious/inflammatory conditions may provide a facilitating substrate for such an excessive sleep myoclonus, as previously demonstrated for some NREM sleeprelated disorders 40,41 and as evident in EV71 infections in which an excessive myoclonus, particularly during sleep onset but often occurring throughout the sleep phase, is a common presenting clinical sign. 23 In conclusion, we suggest that both myoclonic jerks with fever or following an infectious illness could be described as parainfectious myoclonic jerks and they represent a not so common and often unrecognized transitory phenomenon. Therefore, it is important to report cases such ours, to increase the knowledge and the ability of the clinicians to make a correct diagnosis, to avoid unnecessary testing and to distinguish this benign form from other less harmless conditions.…”
Section: Discussionmentioning
confidence: 73%
“…These features seem to be similar to those of febrile seizures and might suggest that febrile myoclonus and febrile seizures are an expression of the same predisposing factors. 7,10,11 In the literature, there are also reported some cases of transitory myoclonus without fever that occurred following an infectious event, such as influenza or chicken pox 13 or gastrointestinal infections by Enterovirus 71 (EV71) 14,23 and even after infections of the upper respiratory tract (presumably of viral origin) or influenza-like syndromes, always benign and with positive prognosis [24][25][26] (see ►Table 2). In our first two cases, given the positive indices of SBEA infection, you might think of a postinfectious etiology.…”
Section: Discussionmentioning
confidence: 99%